Potensi Teknologisasi Pada Zakat, Wakaf Dan Sukuk Dalam Rangka Efisiensi Pertumbuhan Ekonomi - Falah Muhammad Fajrul; Fitrianto Achmad Room (Jurnal Ilmiah Ekonomi Islam, 2023)
Indonesia is predicted to be the country with the fourth most active smartphone users in the world after China, India and America. However, large numbers are not effective in increasing economic growth if you do not take advantage of blockchain technology that can be used via smart phones. The purpose of this research is to look at the potential of blockchain technology in zakat, waqf and sukuk in order to encourage efficiency in economic growth. The research method is library research. The results of the study show that the potential for philanthropic contributions in increasing economic growth through zakat, waqf and sukuk can be more efficient. So utilizing blockchain technology is expected to accelerate economic growth, by technically combining blockchain technology in zakat, waqf and sukuk.